2022
DOI: 10.3389/fcell.2021.802204
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Roles of F-BoxProtein3 in Regulation of Various Cellular Functions

Abstract: Accumulated evidence shows that the F-box protein 3 (FBXO3) has multiple biological functions, including regulation of immune pathologies, neuropathic diseases and antiviral response. In this review article, we focus on the role of FBXO3 in inflammatory disorders and human malignancies. We also describe the substrates of FBXO3, which contribute to inflammatory disorders and cancers. We highlight that the high expression of FBXO3 is frequently observed in rheumatoid arthritis, leukemia, pituitary adenoma, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…1A). These proteins have previously been shown to regulate gene transcription (12, 16, 28, 29). The observation of OGT with SAP25 is also consistent with several investigations that suggest that Sin3 complex, SAP25, OGT, and TET family proteins (TET1, TET2, and TET3) collaborate in regulating transcription (12, 14, 16, 30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). These proteins have previously been shown to regulate gene transcription (12, 16, 28, 29). The observation of OGT with SAP25 is also consistent with several investigations that suggest that Sin3 complex, SAP25, OGT, and TET family proteins (TET1, TET2, and TET3) collaborate in regulating transcription (12, 14, 16, 30).…”
Section: Resultsmentioning
confidence: 99%
“…1A). Among these, we found that SAP25 captures components of the E3 ubiquitin ligase SCF(FBXO3), which promotes ubiquitination (29). SCF(FBXO3) is built from the substrate recognition protein FBXO3, the adaptor protein SKP1, the cullin CUL1, and a small (12 kDa) ring-box protein RBX1 (29).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we probed that miR‐219a‐5p exerted its protective effect on KOA by reducing FBXO3 via binding to the 3′ UTR region. FBXO3 possesses multiple biological functions, such as antiviral response and regulation of neuropathic diseases 24 . However, its function in osteoarthritis is still rarely uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…A review study has been suggested that FBXO3 is highly expressed in the synovial tissues of rheumatoid arthritis. According to the function of FBXO3 regulating the cell cycle, the review study speculates that FBXO3 may modulate rheumatoid arthritis progression by regulating the proliferation as well as survival of rheumatoid arthritis synovial fibroblast 24 . Additionally, it has been suggested that the inhibitor of FBXO3 can diminish the release of IL‐18 as well as IL‐1β in human inflammatory cells through a series of complex processes 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation